Effects of Changes in the Discount Rate on the Foreign Exchange Value of the Dollar: 1973 to 1978 - Brown, Kathleen Hope (Quarterly Journal of Economics, 1981)
Journal Article Effects of Changes in the Discount Rate on the Foreign Exchange Value of the Dollar: 1973 to 1978 Get access Kathleen Hope Brown Kathleen Hope Brown Division of International Finance, Board of Governors of the Federal Reserve System Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 96, Issue 3, August 1981, Pages 551–558, https://doi.org/10.2307/1882687 Published: 01 August 1981